Modern breakthroughs in science: a pragmatic approach (Review article) - Yunus, Kamaruzzaman; Hashi, Abdurezak Abdulahi; John, Akbar (Revelation and Science, IIUM, 2014)
Scientific breakthroughs have to some extent helped man’s understanding of the laws of nature. However, scientific breakthroughs have raised some philosophical and moral concerns among ethicists as well as scientists. This is because, while scientific breakthroughs are worthwhile, nevertheless, in the prospect of putting scientific achievements into prospective, philosophical concerns have been raised about the position of science in man’s stock of knowledge, particularly the authority of science and its relation to other sources of knowledge. These concerns are related to whether or not science constitutes the only genuine source of true knowledge, in such a way that methods of science are preferable over other sources of knowledge. Second, besides the philosophical concerns about the modern progress of science, questions about the place of moral values in modern and contemporary scientific breakthroughs form another matter of concern among many scientists and scholars of ethics. One of the primary questions of this concern is related to whether or not scientific progress ought to be limited to what man ought to do? Similar question is raised about the relationship between the application of science and moral values. This paper intends to explain the need for wasatiyyah (pragmatic) approach in answering these and other questions related to the progress of science.